Given
"y' +\\left( \\frac{x}{1-x^2}\\right)y=xy^{1\/2}"
This is a Bernoli equation , multiply both sides by "y^{-1\/2}" then
"y^{-1\/2}y' +\\left( \\frac{x}{1-x^2}\\right)y^{1\/2}=x"
Let "z=y^{1\/2},\\ \\ \\ \\ \\ ,z'= \\frac{1}{2}y^{-1\/2}y'" , then
"2z' +\\left( \\frac{x}{1-x^2}\\right)z=x\\\\\nz' +\\frac{1}{2}\\left( \\frac{x}{1-x^2}\\right)z=\\frac{x}{2}"
This is a linear equation with integral coefficient
"\\mu= e^{\\int\\left( \\frac{ x}{2(1-x^2)}\\right)dx }\\\\\n\\ \\ \\ \\ = e^{-\\frac{1}{4}\\ln (1-x^2)}\\\\\n\\ \\ \\ \\ =(1-x^2)^{-1\/4}"
Then the general solution is
"\\mu z \\ \\ \\ \\ \\ \\ \\ \\ = \\frac{1}{2} \\int \\mu (x)dx\\\\\n(1-x^2)^{-1\/4}z= \\frac{1}{2} \\int x(1-x^2)^{-1\/4}dx\\\\\n(1-x^2)^{-1\/4}z=-\\frac{1}{3}\\left(1-x^2\\right)^{\\frac{3}{4}}+C\\\\\n (1-x^2)^{-1\/4}\\sqrt{y}=-\\frac{1}{3}\\left(1-x^2\\right)^{\\frac{3}{4}}+C"
Since "y(0)=1\\ \\ \\ \\to C= \\frac{4}{3}"
"(1-x^2)^{-1\/4}\\sqrt{y}=-\\frac{1}{3}\\left(1-x^2\\right)^{\\frac{3}{4}}+\\frac{4}{3}\\\\\n\\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\sqrt{y}= \\frac{-1}{3}(1-x^2) +\\frac{4}{3}(1-x^2)^{1\/4}\\\\\n\\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ \\ y=\\left[ \\frac{-1}{3}(1-x^2) +\\frac{4}{3}(1-x^2)^{1\/4}\\right]^2"
Comments
Leave a comment